(untitled) (International Journal of Engineering and Computer Science, 2015)
Frequent Pattern Mining is a simple Point Of Sale Application for any Supermarket which has a good amount product and a point of sale billing. The paper is on Frequent Pattern Mining Billing. Frequent Pattern Mining is the place where customers come to purchase their daily using products and pay for that. So there is a need to calculate how many products are sold and to generate the bill for the customer. In my paper I have 3 users. First is the data entry operator who will enter the products in database. Second one is the administrator who can see the report of any product. Third one is the bill calculating operator who will calculate the bill and print.